Slitundersökning för jordbearbetning och sådd - Rehn, Claes; Staaf, Niklas (2008)
In this study we try to focus on the costs for wear parts on different type of soil tillage machines and at Väderstad Rapid drilling machine. We have studied some of the leading types of cultivators and disk harrows. Among the cultivators we have investigated Väderstad Cultus, Dalbo Dinkomax, Horsch Tiger and Terrano. At disk harrow we have looked at Amazone Catros and Väderstad Carrier.